Computer program for domestic cold water system / Yusri Mian and Mazlan Yusoff - Mian, Yusri; Yusoff, Mazlan (1997)
Designing the domestic cold water supply system is one of the Mechanical engineering area in building services. The most important design objective in sizing the water supply system is the satisfactory supply of potable water to all fixture. The method of designing this system is basically done by manual calculation and referring to guide book, however today, there are several software available in the market that can be use in designing a water supply system. This will make our jobs easier and not take to much time to design a suitable system in a certain building. In this project, we actually try to build our own program that can also be able to help in designing the water supply system. To make an excellent program is not an easy task, we must first study the Domestic cold water system and clearly understand all the steps and calculations related. Selection and majoring the computer language used, is one of the factors that would give a good and fully graphics output in the program. Since our background knowledge in computer language is FORTRAN 77, we decided to use the QBASIC language which similar to FORTRAN 77 and available in every PC's . Of course, this program cannot compete and not as good as other big program in the market, but at least it would also be use in designing the water supply system. By doing this project also, we can learn and understand more details how to design the water supply system and perhaps this program will be the first step on another program of engineering problems.